"That Tesla of ours": Modular nationalism and the cult of Nikola Tesla. Issue 2 (9th August 2021) - Larson, Ethan
Abstract: This paper uses a comparative case study of Nikola Tesla's use as a symbol in interwar Yugoslavia and the contemporary United States to build upon Anderson's theory of modular nationalism. The modularity of national symbols, I argue, is driven by their utility in addressing similar social, political and economic transformations in different countries and may be transmissible through emigrant communities—albeit not without some changes in substance. Just as Yugoslavia used Tesla to bridge ethnic divisions, Yugoslav emigrants deployed Tesla to enhance their status in the United States. The cult of Tesla, moreover, is doubly modular, with its Yugoslav incarnation drawing inspiration from the American cult of Thomas Edison, just as Edison's current obsolescence as a symbol led to the cult of Tesla's adoption in the United States.